MULTIPERIQDICITY OF RR LYRAE STARS. T SEXTANTIS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
The Fourier analyses performed for 401 photoelectric V-magnitudes of the RRc Lyrae variable T Sex (Barnes III et al.) show that the star may be multiperiodic with most significant frequency f1H frequencies multiple to that of f1H as well as to frequencies fg and fs introduced by us.